Exploratory analysis of Spirulina platensis LB 2340 growth in varied concentrations of anaerobically digested pig effluent (ADPE). Issue 9 (September 2021) - Baker, Matthew; Blackman, Sam; Cooper, Erin; Smartt, Kevin; Walser, David; Boland, Megan; Kolar, Praveen; Beck, Ashley E.; Chinn, Mari S.
Abstract: There is a significant interest in novel waste management solutions to treat wastewater from swine operations. Anaerobic digestion is a rising and prominent solution, but this technology still generates highly concentrated effluent that requires further remediation. Therefore, the aim of this study was to explore the feasibility of cultivating the cyanobacterium Spirulina platensis in swine effluent for future applications in biological waste treatment and value-added fermentation. To accomplish this goal, growth of S. platensis was characterized in varying proportions of ideal, synthetic Zarrouk medium and anaerobically digested pig effluent (ADPE) to obtain growth rate models. Results yielded a positive correlation between S. platensis growth rate and Zarrouk medium proportion, with the highest growth rate in 100% Zarrouk media but comparable growth in the 50/50% Zarrouk/ADPE mixture. This study demonstrates the potential for S. platensis to further improve the treatment efficacy of anaerobic digestion systems, and the exploratory analysis also highlights that further testing is required to investigate possible carbon availability, chemical inhibition, and overall nutrient reduction in ADPE. This research contributes important data toward the feasibility of producing value-added cyanobacterial biomass while simultaneously consuming excess nutrients to aid in agricultural wastewater management efforts and generate cost-effective products in a more sustainable manner. Abstract : Spirulina ; Cyanobacteria; Swine effluent; Anaerobic digestion, Biomass production.